Effect of yeast strain and some nutritional factors on tannin composition and potential astringency of model wines. (February 2016) - Rinaldi, Alessandra; Blaiotta, Giuseppe; Aponte, Maria; Moio, Luigi
Abstract: Nine Saccharomyces cerevisiae cultures, isolated from different sources, were tested for their ability to reduce tannins reactive towards salivary proteins, and potentially responsible for wine astringency. Strains were preliminary genetically characterized and evaluated for physiological features of technological interest. Laboratory-scale fermentations were performed in three synthetic media: CT) containing enological grape tannin; CTP) CT supplemented with organic nitrogen sources; CTPV) CTP supplemented with vitamins. Adsorption of total tannins, tannins reactive towards salivary proteins, yellow pigments, phenolics having antioxidant activity, and total phenols, characterizing the enological tannin, was determined by spectrophotometric methods after fermentation. The presence of vitamins and peptones in musts greatly influenced the adsorption of tannins reactive towards salivary proteins (4.24 g/L gallic acid equivalent), thus promoting the reduction of the potential astringency of model wines. With reference to the different phenolic classes, yeast strains showed different adsorption abilities. From a technological point of view, the yeast choice proved to be crucial in determining changes in gustative and mouthfeel profile of red wines and may assist winemakers to modulate colour and astringency of wine. Highlights: Adsorption ability of phenolics by yeasts during fermentation was evaluated. Nutritional factors of must greatly influenced phenolic adsorption by yeasts. Reduction of astringent tannins is influenced by yeasts and medium composition. Wine astringency can be reduced by yeast during fermentation of tannin-rich musts.